Harps on the ancient silk road - B. Lawergren (Nomadic Civilization: Historical Research, 2022)
One can derive a great deal of information on Chinese music from images painted during the first millennium along the Silk Road, including Dunhuang, especially if combined with Chinese texts. Long before the arrival of Buddhism in China, music held an important place in Confucian and Daoist ritual. With the arrival of Buddhism, its followers demanded no less, but they required instruments quite different from the ritual instruments used during the first millennium b.c.e. — bronze bells, stone chimes, and large drums. The instruments brought by Buddhists were light (lutes, harps, flutes, reed instruments, and small drums). Most survived in China, but harps (konghou) disappeared shortly after 1000 c.e. as Buddhism declined. One of the last depictions of harps is found in cave 465 at the Mogao Grottoes (thirteenth century). This paper attempts to compile what is known about these ancient instruments, information vital to conservators, art historians, instrument makers, and musicians who wish to revive earlier practice. Harps died out in China, but replicas are now played in several places, for example, the Dunhuang Academy, the Shanghai Conservatory, Jeonju (Korea), and Tokyo.